2002
DOI: 10.3402/meo.v7i.4534
|View full text |Cite
|
Sign up to set email alerts
|

Epistemological Beliefs and Knowledge among Physicians: A Questionnaire Survey

Abstract: Background: All sciences share a common underlying epistemological domain, which gives grounds to and characterizes their nature and actions. Insofar as physicians depend on scientific knowledge, it would be helpful to assess their knowledge regarding some theoretical foundations of science. Objectives: 1.To assess resident physicians' knowledge of concepts and principles underlying all sciences. 2. To determine, to what extent physicians' epistemological beliefs and attitudes are compatible with the scientifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Indeed, according to Sandoval (2004), although complexity of NOS conceptions increases with exposure to science, its principles, and its methods, secondary school and even university students display naïve understandings of NOS. For example, Pena, Paco, and Peralta (2002) found that the understanding of science exhibited by medical practitioners was clearly at variance with most current conceptions of scientific practice in that discipline.…”
mentioning
confidence: 99%
“…Indeed, according to Sandoval (2004), although complexity of NOS conceptions increases with exposure to science, its principles, and its methods, secondary school and even university students display naïve understandings of NOS. For example, Pena, Paco, and Peralta (2002) found that the understanding of science exhibited by medical practitioners was clearly at variance with most current conceptions of scientific practice in that discipline.…”
mentioning
confidence: 99%
“…In addition, Pena and Paco showed majority of medical students did not read or follow any sources related to science for a five-year long period and did not know definition and aspects of science [10]. Again, Pena, Paco and Peralta found that no physicians knew the pre-assumptions of science and majority of them did not know definition of scientific theory [11]. Graduate level studies about the aspects of the NOS in medical context were not found in the literature.…”
Section: Importance Of Biological Literacy and Nos For Graduate Medicmentioning
confidence: 97%
“…Epistemology, derived from the combination of the Greek words "episteme" meaning "knowledge" and "logos" meaning "word, reason, science, explanation, and theory", is a branch of philosophy that directly deals with the concept of knowledge [2,3]. Epistemology is a branch that investigates the source, nature, and scope of human knowledge, as well as the criteria for determining what constitutes true knowledge or truth [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In the development of EB, several factors can influence them, including age, gender, education, family structure, culture, parents' educational level, LOC, place of residence, field of study, and cognitive development (intelligence) [4,8,9,24,[40][41][42][43][44][45][46]. One of the factors that affect students' EB is LOC, which is among the individual characteristics.…”
Section: Introductionmentioning
confidence: 99%